Implementasi Penggunaan Komik Keteladanan KH. A. Wahab Hasbullah Sebagai Upaya Menurunkan Angka Alpa Anak Asuh di Lingkungan Panti Asuhan Assolihin Candi Mulyo Jombang - Lia Yukhoiro; Rina Dian Rahmawati (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to examine the implementation of the use of KH Wahab Hasbullah's exemplary comic as an effort to reduce the number of harps, foster children who skip early school in the Ashholihin Orphanage, Mulyo Temple, Jombang. The approach used in this study is qualitative, with a data collection method through in-depth interviews with foster children, dininah teachers, and orphanage administrators. The results of the interview show that the use of exemplary comics by KH. A Wahab Hasbullah has a positive impact in increasing the interest and motivation of foster children to participate in early childhood activities. The foster children stated that the stories and illustrations in the comic were easy to understand and provided inspiration to follow in KH's footsteps. A. Wahab Hasbullah. Teachers also observed an increase in the participation and discipline of foster children after the introduction of the comic. The orphanage management noted a significant decrease in the number of alpa foster children in the implementation of this exemplary comic. Thus, the use of exemplary comics by KH. A. Wahab Hasbullah has proven to be effective as an educational medium that can reduce the number of foster children in participating in early childhood activities at the Assholihin Orphanage, Mulyo Temple, Jombang This study suggests that other orphanages can consider the use of similar alternative media to increase the participation of foster children in educational and religious activities.